Unraveling the Traffic Congestion Due to Bottleneck: A Review - Mainali, Saras; Regmi, Swapnil; Wagle, Kapil; Bhele, Raju (International Journal on Engineering Technology, 2024)
In the metropolitan cities across the world, traffic congestion is a major problem due to growing urbanization, vehicle growth and infrastructure constrains. Bottleneck congestion is a major problem faced in traffic management in many urban centers as it affects travel time, emissions, and fuel consumption. It accounts for nearly 40% of congestion. This extensive literature review aims to discuss the main reasons behind traffic congestion, classify their patterns, and discuss how it can be detected and prevented. This paper focuses on the economic and social consequences of traffic bottlenecks by considering several traffic congestion research. The methods namely; Manual counting, social surveys, CCTV footage analysis, Navigation, and simulation software namely VISSIM are discussed in this paper. It also offers traffic control methods and other difficulties and contemporary control measures for congestion. In addition, this review emphasizes on the need of cost effective traffic congestion management, particularly in underdeveloped countries like Nepal, where video graphic survey is recommended as the most feasible approach. The purpose is to deliver pertinent information to transportation planners and engineers to address issues concerning traffic congestion in big cities and offer ways of improving the efficiency of transport systems in urban cities.